Anatomy and Morphology Study of Agronomy between Healthy Soybean to Soybean infected with Cowpea mild mottle virus and its Utilization as Vocational High School Subjects - As’ad Syamsul Arifin (Pascasarjana Universitas Negeri Malang (UM), 2013)
Kajian Morfologi Anatomi dan Agronomi antara Kedelai Sehat dengan Kedelai Terserang Cowpea Mild Mottle Virus serta Pemanfaatannya sebagai Bahan Ajar Sekolah Menengah KejuruanAbstract: One of the causes of low productivity of soybean in Indonesia is the virus attack of Cowpea mild mottle virus (CPMMV). This study is a survey research that aims to describe and collect information about the study of the morphology, anatomy and agronomy to infection of CPMMV between varieties infected with uninfected. The Data is analyzed by ussing descriptive and Inferential ANOVA using SPSS for Windows version 16. The results shows: Varieties in gumitir is healthy, Anjosmoro is healthy, Mahameru is healthy, MLGG 0021, and MLGG 0268 has a larger size in terms of leaf length, leaf width, length leaf petiole, the leaf ratio (L / W), and the ratio of leaf (L / PL) compared varieties sick. Argopuro varieties of pain have a larger size in terms of leaf length, leaf width, leaf petiole length and leaf ratio (L / W), leaf ratio (L / PL) compared to healthy varieties. There is no color difference hipokotil, differences leaf shape, leaf color, fur color stem, leaf surface between healthy and diseased soybeans in six varieties. There are differences in seed color, the color of ripe pods, between healthy and diseased soybeans in six varieties. Color flower on the fifth soybean varieties of healthy and diseased purple, except in gumitir white varieties. There are differences in leaf shape on the variety Argopuro, Anjosmoro, Mahameru healthy and infecetd. There is no difference in shape between healthy and diseased leaves on gumitir varieties, MLGG MLGG 0021 and 0268. There is the influence of varieties, conditions, interaction varieties and conditions of the leaf cell size. There are varieties effect on the number of stomata, conditions and interactions varieties and conditions do not significantly affect the number of stomata. There is no influence of varieties, interaction varieties and conditions of the number of epidermis. The number of trichomes healthy soybean varieties more than soybean varieties sick. There is the influence of varieties, the conditions on plant height, there is no interaction effect of varieties and conditions of the plant height. There is no influence of varieties, conditions, interaction varieties and conditions of the empty pods. Empty pods soy soybeans healthy at 0.55 times the sick. There is the influence of varieties, conditions, interaction varieties and conditions of the pods. There is the influence of varieties, conditions, interaction varieties and conditions of the fertile books. There is the influence of varieties, conditions, interaction varieties and conditions of the number of pods. There is the influence of varieties, conditions, interaction varieties and conditions of the number of books. There is a heavy influence on the condition of the pod. No influence of varieties, interaction varieties and conditions of the heavy pods. There is the influence of varieties, conditions, interaction varieties and conditions of the number of seeds. Key Words: soybean, CPMMV, infected plants, healthy plants Abstrak: Salah satu penyebab rendahnya produktivitas kedelai di Indonesia adalah serangan virus belang samar kacang tunggak Cowpea mild mottle virus (CPMMV). Penelitian ini adalah penelitian survei yang bertujuan untuk menggambarkan dan mengumpulkan informasi tentang kajian morfologi, anatomi dan agronomi terhadap infeksi CPMMV antara varietas yang terinfeksi dengan yang tidak terinfeksi. Data dianalisi secara deskriptif dan secara Inferensial ANAVA dengan menggunakan pro-gram SPSS for Windows versi 16. Hasil penelitian menunjukkan: Varietas Gumitir sehat, Anjosmoro sehat, Mahameru sehat , MLGG 0021, dan MLGG 0268 memiliki ukuran lebih besar dalam hal panjang daun, lebar daun, panjang petiol daun, nisbah daun (L/W), dan nisbah daun (L/PL) dibandingkan va-rietas yang sakit. Varietas Argopuro sakit memiliki ukuran lebih besar dalam hal panjang daun, lebar daun, panjang petiol daun, dan nisbah daun (L/W), Nisbah daun (L/PL) dibandingkan varietas yang sehat. Tidak terdapat perbedaan warna hipokotil, perbedaan bentuk daun, warna daun, warna bulu batang, permukaan daun antara kedelai sehat dan sakit pada keenam varietas. Terdapat perbedaan warna biji, warna polong masak, antara kedelai sehat dan sakit pada keenam varietas. Warna bunga pada kelima varietas kedelai sehat dan sakit berwarna ungu, kecuali pada varietas Gumitir berwarna putih. Terdapat perbedaan bentuk daun pada varietas Argopuro, Anjosmoro, Mahameru sehat dan sakit. Tidak terdapat perbedaan bentuk daun antara sehat dan sakit pada varietas Gumitir, MLGG 0021 dan MLGG 0268. Ada pengaruh varietas, kondisi, interaksi varietas dan kondisi terhadap ukuran sel daun. Ada pengaruh varietas terhadap jumlah stomata, kondisi serta interaksi varietas dan kondisi tidak berpengaruh secara nyata terhadap jumlah stomata. Tidak terdapat pengaruh varietas, interaksi varietas dan kondisi terhadap jumlah epidermis. Ada pengaruh kondisi terhadap jumlah epidermis. Jumlah trikoma varietas kedelai sehat lebih banyak daripada varietas kedelai sakit. Ada pengaruh va-rietas, kondisi terhadap tinggi tanaman, tidak terdapat pengaruh interaksi varietas dan kondisi terhadap tinggi tanaman. Tidak terdapat pengaruh varietas, kondisi, interaksi varietas dan kondisi terhadap polong hampa. Polong hampa kedelai sehat sebesar 0,55 kali kedelai sakit. Ada pengaruh varietas, kondisi, interaksi varietas dan kondisi terhadap polong isi. Ada pengaruh varietas, kondisi, interaksi varietas dan kondisi terhadap buku subur. Ada pengaruh varietas, kondisi, interaksi varietas dan kondisi terhadap jumlah polong. Ada pengaruh varietas, kondisi, interaksi varietas dan kondisi terhadap jumlah buku. Ada pengaruh kondisi terhadap berat polong. Tidak ada pengaruh varietas, interaksi varietas dan kondisi terhadap berat polong. Ada pengaruh varietas, kondisi, interaksi varietas dan kondisi terhadap jumlah biji. Kata kunci: tanaman kedelai, CPMMV, tanaman terinfeksi, tanaman sehat